2013
DOI: 10.4067/s0718-19572013000300017
|View full text |Cite
|
Sign up to set email alerts
|

Diet plasticity of the South American sea lion in Chile: stable isotope evidence

Abstract: Resumen.-Estudios de dieta del lobo marino común (LMC) en Chile sugieren que esta especie es un depredador oportunista y generalista, cuya dieta varía dependiendo de la distribución de las especies presas y de las varia ciones espaciotemporales en la abundancia de dichas presas. Sin embargo, estos estudios han sido esporádicos, limitados espacialmente y basados en análisis de contenidos estomacales, lo que no permite un análisis integral de la compos ición de la dieta y de sus potenciales diferencias espacio-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
4
20
0
4
Order By: Relevance
“…SAFS feed mainly on Engraulis anchoita, Anchoa marinii, Cynoscion guatucupa, as several cephalopod species (Naya et al, 2002). In Falkland Islands (UK) and Chile, the diet is a bit different but always is constituted mostly by similar fishes (Baylis et al, 2014;Casper et al, 2006;Muñoz et al, 2013). For example, SAFS is a flexible forager and have a consumption of a wide range of prey, often more of 20 taxa (Casper et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAFS feed mainly on Engraulis anchoita, Anchoa marinii, Cynoscion guatucupa, as several cephalopod species (Naya et al, 2002). In Falkland Islands (UK) and Chile, the diet is a bit different but always is constituted mostly by similar fishes (Baylis et al, 2014;Casper et al, 2006;Muñoz et al, 2013). For example, SAFS is a flexible forager and have a consumption of a wide range of prey, often more of 20 taxa (Casper et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…appears dominated by few species, but these change seasonally and interanually (Hume et al, 2004;Klages and Bester, 1998;Naya et al, 2002). In the same sense, SASL as generalist and opportunist feeder is capable of change their diet in response the availability of preys or for temporal variation of preys (Muñoz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of sea lions (including pups) in the Cobquecura colony has remained relatively constant for the last 12 yr (Quiñones et al 2011), while the abundance of sea lions (especially pups) in the PP/PN colonies (particularly in Punta Negra) has decreased in the last 15 yr (Sielfeld & Guz mán 2002). These differences in population trends between the areas cannot be explained by diet composition, because sea lions from the 2 colonies are both important consumers of common sardine and anchovy (Sielfeld 1999, Muñoz et al 2013, showing a clear pattern of epipelagic and coastal foraging (Hevia 2013, Hückstädt et al 2014. In addition, no effect of prey energetic content is expected on sea lion populations because these 2 prey species are of a similar size and have a similar diet composition, suggesting a similar utilization of re sources and energetic content (Llanos et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Data were log 10 transformed for analysis. We analyzed the biomass of 2 pelagic clupeid species: anchovy Engraulis ringens and common sardine Strangomera bentincki, which are considered to be the most economically important resources for both industrial and small-scale fisheries in north and central-south Chile (Gutiérrez-Estrada et al 2007, Castillo-Jordán et al 2010, and commonly reported as one of the most important prey species in the diet of the South American sea lion in Chile, both in the north (> 90% of diet composition; Sielfeld 1999) and in the central-south (30 to 60% of diet composition; Muñoz et al 2013). Density and fish biomass data were obtained from acoustic surveys carried out onboard the RV 'Abate Molina', a stern trawler 43.2 m long and with 1400 HP.…”
Section: Estimation Of Prey Availabilitymentioning
confidence: 99%
“…Along the Atlantic coast, this species is distributed from the south of Torres in Brazil (Rosas et al 1994) to Tierra del Fuego in Argentina (King 1983, Dans et al 2012, as well as the Falkland/Malvinas and Isla de los Estados (Osgood 1943, Bastida & Rodríguez 2003. Typically piscivorous (Vaz-Ferreira 1982, Crespo et al 1997, this species has a varied diet including crabs, cephalopods (mollusks), squid and gastropods (Aguayo & Maturana 1973, George-Nascimento et al 1985, Sielfeld et al 1997, Aguayo-Lobo et al 1998, Hückstädt & Antezana 2006, Hückstädt et al 2007, De la Torriente et al 2010, Muñoz et al 2013. However, the main dietary items of these animals are largely determined by the prey species available in their habitat, making them opportunistic predators (Sielfeld et al 1997, Koen-Alonso et al 2000.…”
Section: Introductionmentioning
confidence: 99%